Recent Advances in Efficient Photocatalytic Degradation Approaches for Azo Dyes - Arpita Paul Chowdhury; K. S. Anantharaju; K. Keshavamurthy; Samuel Lalthazuala Rokhum (Journal of Chemistry)
In recent decades, the textile industry has contributed to continuous pollution in the environment. Synthetic dyes which are commonly found in waste water are azo, sulfur, anthraquinone, triphenylmethyl, indigoid, and phthalocyanine derivatives. These pollutants block the light penetration in water bodies and prevent photosynthesis activity, thereby affecting aquatic life. As an environmental crisis, several technologies have been explored to control pollution. Among all the techniques, the photocatalysis process is considered as a green, simple, and economical process. To improve the photocatalytic activity, researchers worldwide have investigated various photocatalysts such as metal oxides, metal ferrites, and heterostructured nanocomposites. The major goal of this review article is to propose a high-performing, cost-effective hybrid photocatalyst reported to date for prospective azo dye pollutant remediation. This review article also aimed to highlight the challenges and uncertainties associated with dye degradation in the photocatalytic process.